Mediating of Job Satisfaction and Employee Engagement in the Relationship between Soft-Training and Development Investment Towards Employee Turnover - Hoo, Wong Chee; Shien, Lee Yan; Wolor, Christian Wiradendi; Shaznie, Aminath; Prompanyo, Manoch (Journal of Ecohumanism, 2024)
This study examines the impact of soft training and development initiatives on employee engagement, job satisfaction, and employee turnover, with a particular focus on the mediating role of job satisfaction. Utilizing purposive sampling, the research gathered data from diverse industries through online surveys, focusing on participants' experiences with training and development programs. The study employed descriptive analysis and regression analysis using SPSS to explore the relationships between the variables. Multiple regression and mediation analyses were employed to test the proposed hypotheses. The findings indicate a significant positive relationship between soft training and job satisfaction, suggesting that soft training initiatives enhance employees' job satisfaction. Additionally, a negative relationship was observed between job satisfaction and turnover intentions, indicating that higher job satisfaction is associated with lower turnover intentions. The mediation analysis revealed that job satisfaction partially mediates the relationship between soft training and turnover intentions. This implies that while soft training directly reduces turnover intentions, it also indirectly contributes to this reduction by enhancing job satisfaction. These results underscore the importance of investing in soft training programs to foster job satisfaction and subsequently reduce employee turnover. This study contributes to the existing literature by highlighting the critical role of job satisfaction as a mediator in the relationship between training and development initiatives and turnover intentions. Practical implications for HR practitioners and organizational leaders include the strategic implementation of soft training programs to enhance job satisfaction and minimize turnover, thereby promoting a more stable and engaged workforce.